Waste-to-Energy : Technologies and Project Implementation - Rogoff, Marc J.; Screve, Francois (Elsevier professional, 2011)
This book covers in detail programs and technologies for converting traditionally landfilled solid wastes into energy through waste-to-energy projects. Modern Waste-to-Energy plants are being built around the world to reduce the levels of solid waste going into landfill sites and contribute to renewable energy and carbon reduction targets. The latest technologies have also reduced the pollution levels seen from early waste incineration plants by over 99%. With case studies from around the world, Rogoff and Screve provide an insight into the different approaches taken to the planning and implementation of WTE. The second edition includes coverage of the latest technologies and practical engineering challenges as well as an exploration of the economic and regulatory context for the development of WTE.
Keywords: Incineration.; Refuse and refuse disposal.; Refuse as fuel.; Waste products as fuel.; elektronické knihy; electronic books